2011
DOI: 10.1007/s10926-011-9289-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Rehabilitation in Singapore and Malaysia

Abstract: Even though Malaysia and Singapore are two different countries, in many ways their current provision of occupational rehabilitation services and the problems they face with are very similar. There is a lot of room for systemic improvements that require government support and action. Most prominently, the training of more healthcare professionals in the assessment and rehabilitation of the injured worker should be encouraged. There could be better liaison between the many stakeholders and more funding made avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There were also 6 papers identified describing CR but they did not report primary data (Germany, Hong Kong, Singapore, Switzerland and Thailand [34][35][36][37][38][39] ). These publications were summarized in the text only.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…There were also 6 papers identified describing CR but they did not report primary data (Germany, Hong Kong, Singapore, Switzerland and Thailand [34][35][36][37][38][39] ). These publications were summarized in the text only.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Comparing the occupational rehabilitation programs in Malaysia and Singapore, it was found that there are serious gaps in the continuous process from clinical care of injured workers to rehabilitation (in preparation for return-to-work) [8]. It is recommended that comprehensive development and coordination of rehabilitation for RTW programs that incorporate both clinical and community-based facilities.…”
Section: A Rehabilitation and Therapymentioning
confidence: 99%
“…of stakeholders At present, the current legislations governing workplace safety and health in Singapore are focused on accident rates, work injury incidences and claim amounts [1,2]. Though RTW is a primary measure of the effectiveness of workers' compensation system [11], there is an absence of a work injury management framework to guide various stakeholders on achieving positive RTW outcomes in Singapore [29]. Thus stakeholders tend to focus more on the process of compensation, rather than rehabilitation back to work, after a work injury.…”
Section: Legislation and Policy Awarenessmentioning
confidence: 99%
“…Thus, referrals for RTW services are dependent on the individual primary physician's level of knowledge and awareness of occupational rehabilitation. For injured workers with more severe disabilities, they may be referred to community rehabilitation agencies for vocational assessment, training and placements [29]. There is a potential for the hospital-based RTWC model of care to coordinate and synergise the existing range of occupational rehabilitation services available in the hospital and community settings and to establish more comprehensive care for injured workers.…”
Section: Coordination and Synergy Of Servicesmentioning
confidence: 99%